2017
DOI: 10.4094/chnr.2017.23.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Child Development Knowledge, Rearing Knowledge and Use of Health Care Service on Maternal Confidence among Mothers with Premature Infants

Abstract: The purpose of this study was to examine how child development knowledge, child rearing knowledge, and use of healthcare services after discharge affect maternal confidence among mothers of premature infants. Methods: Participants in this study were 55 mothers who were involved in internet communities for mothers with premature infants and 30 mothers who visited hospitals for follow up care after having their babies discharged from Neonatal Intensive Care Units (NICU) in South Korea. Results: Presence of opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a qualitative study of mothers' experiences regarding attachment toward their lowbirthweight infants in a follow-up program, mothers identified that receiving limited information was a major barrier for forming attachments to their infants [11]. Knowledge of child development by the mothers of premature infants is a significant predictor for maternal confidence [40], while less knowledge on prematurity development than rearing and high educational interest in the development has been examined in a descriptive study in 2013 [41].…”
Section: System-level Challengesmentioning
confidence: 99%
“…In a qualitative study of mothers' experiences regarding attachment toward their lowbirthweight infants in a follow-up program, mothers identified that receiving limited information was a major barrier for forming attachments to their infants [11]. Knowledge of child development by the mothers of premature infants is a significant predictor for maternal confidence [40], while less knowledge on prematurity development than rearing and high educational interest in the development has been examined in a descriptive study in 2013 [41].…”
Section: System-level Challengesmentioning
confidence: 99%
“…Interactions with the caregiver are important in infants’ development because their development is influenced by the external environment [ 4 - 6 ]. After NICU discharge, parents of preterm children experience difficulties in physical and psychological aspects, self-efficacy, interactions with their babies, and parenting behavior [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parents who lack knowledge regarding infants born prematurely are afraid and anxious about caring for their preterm children [ 8 ]. In addition, since preterm infants often require specialized healthcare or readmission after NICU discharge, their parents need systematic and long-term interventions for child-rearing and development after discharge from the NICU [ 4 ]. Therefore, to promote and support the long-term development of preterm children, parents should be included in developmental support care [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%